THE COMPARISON BETWEEN HBA1C AND GLYCATED ALBUMIN LEVELSIN PATIENTS WITH DIABETES MELLITUS TYPE II WITH OR WITHOUT CHRONIC KIDNEY DISEASE - Muhammad Rusli; Zulfikar Zulfikar; Santi Syafril (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
The most appropriate marker to assess the glucose level of diabetes mellitus patient with chronic kidney disease has not been recognized. The reduction of an erythrocyteslifetime will pull down the HbA1c from a patient with chronic kidney disease. Beside HbA1c, Glycated Albumin (GA) is an alternative glycemic marker. The aim of this study is to find out whether there is a comparison of HbA1c and glycated albumin levels in patients with type 2 DM with and without Chronic Kidney Disease (CKD). This research is an observational analytic study with a cross-sectional design. Conducted on 46 patients with DM type 2 with or without CKD at the Adam Malik Hospital, from August 2016 – December 2016 that fulfill the criteria, and after that, the HbA1c and GA were examined. The GA level in patients with DM type II and CKD (18.48±5.23)%, were not significantly different from those patient with DM type II without CKD (17.39±6.07)%. From the statistical test result, there is no significant difference of GA from patient with DM type II with CKD and without CKD (p=0.519)and so does the HbA1c levels in type 2 DM patients with CKD (8.1±1.74)% were lower than those patient with type 2 DM without CKD (8.6±1.67)% although there was no significant difference between  HbA1c level from patients with type 2 DM without CKD and with CKD (p=0.364) from the statistical test result. There is no significant difference between HbA1c level and glycated albumin from patients with DM type II with or without CKD.